Improved Pattern Selection for PDB Heuristics in Classical Planning (Extended Abstract) - Scherrer, Sascha; Pommerening, Florian; Wehrle, Martin (Proceedings of the International Symposium on Combinatorial Search, 2015)
The iPDB approach selects patterns by a local search in the space of pattern collections. This search often gets stuck in local optima, which limits the quality of the resulting heuristic. In this research abstract, we report on current progress to tackle this problem. We investigate variable neighborhood search with encouraging experimental results.